ZVS-PB Discussion Club. SIBIRIAN CODE. Honouring cities - Astrakhantseva, Victoria; Grigoryeva, Elena; Dolnakov, Petr; Dering, Alexander; Zykov, Sergey; Myakota, Alexey; Rybin, Oleg; Khotulev, Ruslan; Khudyakov, Sergey; Tsoi, Valery; Chertilov, Alexey; Lidin, Konstantin; et al. (project baikal, 2023)
On 15 June at 10:30, a discussion club of Zodchestvo in Siberia-Project Baikal (ZVS-PB) was held in the Irkutsk House of the Architect. It was dedicated to the theme of the festival: SIBIRIAN CODE. The round table gathered representatives from Irkutsk, Bratsk, Krasnoyarsk, Kemerovo, Novokuznetsk, Barnaul, Tomsk, Novosibirsk and Nizhny Novgorod. Elena Grigorieva, vice-president of the Union of Architects of Russia for the Siberian Federal District, architect and publisher was the moderator.
Keywords: city identity; stylistics; landscape; wood; taiga civilisation; leaders of organisations of the Union of Architects of the Siberian Federal District